Hallowe'en party : a Hercule Poirot mystery - Christie, Agatha, 1890-1976 (Christie, Agatha, 1890-1976. Hercule Poirot mysteries., 2011)
"At a Hallowe'en party, Joyce--a hostile thirteen-year-old--boasts that she once witnessed a murder. When no one believes her, she storms off home. But within hours her body is found, still in the house, drowned in an apple-bobbing tub. That night, Hercule Poirot is called in to find the 'evil presence.' But first he must establish whether he is looking for a murderer or a doubler murderer ..."--